Ecology and religion - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
In this program, we're going to look at global warming, and the steady extinction of some of our most precious and vital plants and animals. We'll hear from three scholars who believe that our environmental crisis is really a symptom of a spiritual crisis -a crisis of perspective.
Executive producer, Nasuhi Yurt.
Host : MaryLynn Schiavi.
DVD format
Keywords: Ecology; Religions; Ideology